(untitled) (UNED Research Journal, 2023)
“Physical, chemical, and microbiological characteristics of groundwater in Los Chiles, Costa Rica, and its association with land use”. Introduction: Los Chiles has one of the lowest Social Progress Indexes in Costa Rica. The inhabitants drink untreated groundwater from an aquifer across the Nicaragua-Costa Rica border. Objective: To characterize water quality and possible associations with land use. Methods: We collected six water samples from wells during the dry and rainy seasons in 2019 and applied standard tests. Results: Grasslands and bare ground cover larger areas than other land uses. The water is calcic-bicarbonate type, and its physical-chemical values are acceptable, we did not detect Escherichia coli in any sample, while we only detected fecal coliforms in La Trocha. Conclusion: If treated to eliminate coliforms and protected from other effects of human activity, this water will be optimal for human consumption.